Indonesia’s Foreign Policy Transformation: From Authoritarianism to Democratic Diplomacy - Azizah Nur Avicena; Olivia Delaney; Adam Abdul Rahim (Indonesian Political Transformation, 2025)
Indonesia’s foreign policy has undergone a substantial transformation since the Reformasi, moving away from authoritarian foreign diplomacy under the New Order regime to a more democratic and inclusive approach in the post-Suharto era. This paper examines the shift in Indonesia’s foreign policy, focusing on how democratic principles, human rights, and regional cooperation have influenced the country’s diplomatic relations. By analyzing key foreign policy decisions, such as Indonesia’s role in ASEAN, its relations with the United States, China, and neighboring countries, the paper highlights how Indonesia’s democratic transition has reshaped its international positioning. The study also explores the growing role of civil society in shaping foreign policy, as well as the influence of public opinion on Indonesia's international decisions. This research contributes to the field of international relations by examining the dynamic relationship between domestic political transformation and foreign policy, providing insights into how democratization influences a nation’s global engagement.